تقييم سلسلة كامبريدج لمادة الرياضيات للصف الرابع في ضوء الاتجاهات الدولية حول معايير الرياضيات بسلطنة عمان = Evaluation of the Cambridge Mathematics Series for the fourth grade in light of International Trends in Mathematics Standards (TIMSS, 2019) in the Sultanate of Oman - Al-Hudaify, Salim Said Salim; Nik Abdullah, Nik Md. Saiful Azizi; Abdullah Al-Hadidy, Muhammad (Alhikmah Research & Publication Centre, 2025)
هدفت الدراسة إلى تقييم سلسلة كامبريدج لمادة الرياضيات للصف الرابع في ضوء الاتجاهات الدولية حول معايير الرياضيات (TIMSS,2019) بسلطنة عمان . اعتمدت الدراسة المنهج المختلط لتحليل محتوى الكتب وتقييمه باستخدام نموذج ستافلبيم (CIPP) مع الأخذ في الاعتبار الأبعاد المختلفة لمعايير (TIMSS)، وهي: الأعداد، الهندسة، البيانات، والعمليات المعرفية (المعرفة، التطبيق، والاستدلال). تم جمع البيانات من خلال تحليل محتوى الكتب وتوزيع استبيانات على عينة من معلمي ومشرفي الرياضيات. أظهرت النتائج تحقيق الكتب نسبة كبيرة من معايير الأعداد بينما كانت نسبة تحقيق معايير الهندسة والبيانات منخفضة. وأوصت الدراسة بضرورة تطوير المناهج لتتماشى بشكل أكبر مع متطلبات (TIMSS) لتعزيز مستويات التحصيل للطلبة في الرياضيات. _______________________________________________________ The study aimed to evaluate the alignment of the Cambridge Mathematics series for the fourth grade in Oman with the standards of the International Study (TIMSS, 2019). A mixed-methods approach was adopted, employing the CIPP evaluation model to analyze the content of the textbooks and assess their compliance with various TIMSS dimensions: numbers, geometry, data, and cognitive processes (knowledge, application, and reasoning). Data were collected through content analysis and questionnaires distributed to a sample of mathematics teachers and supervisors. The findings revealed a high alignment with the standards for numbers but a lower alignment with geometry and data standards. The study recommended developing the curriculum to better meet TIMSS requirements, thereby enhancing students' mathematics achievement levels.